Democracy and social rights : a path toward equality? - Patriquin, Larry (Routledge, 2025)
Inequality is everywhere, while at the same time, "representative democracy" is under attack. This book considers what we are doing wrong and how we can put it right. The author argues that our inability to create and entrench social rights, which would help make societies more equal, is rooted in the structures of our political institutions and concludes that our politics, regardless of the presence of elections, cannot carry the mantle democratic. This is why substantial social rights are almost nowhere to be seen, especially in "liberal" welfare regimes like the United States and the United Kingdom. The main lesson is that all social-change activists must make the creation of democracy a priority, because without new institutions most of their activism will prove futile. If there are no meaningful changes to our political systems, then decades from now, despite our brilliant blueprints for reform and our frequent marches in the streets, people will find themselves in familiar surroundings, in the same places we are today.
Keywords: Democracy.; Equality.; Social rights.; elektronické knihy; electronic books